A trans-fatty acid-rich diet promotes liver tumorigenesis in HCV core gene transgenic mice. (12th July 2019) - Hu, Xiao; Wang, Xiaojing; Jia, Fangping; Tanaka, Naoki; Kimura, Takefumi; Nakajima, Takero; Sato, Yoshiko; Moriya, Kyoji; Koike, Kazuhiko; Gonzalez, Frank J; Nakayama, Jun; Aoyama, Toshifumi
Abstract: Excess consumption of trans -fatty acid (TFA), an unsaturated fatty acid containing trans double bonds, is a major risk factor for cardiovascular disease and metabolic syndrome. However, little is known about the link between TFA and hepatocellular carcinoma (HCC) despite it being a frequent form of cancer in humans. In this study, the impact of excessive dietary TFA on hepatic tumorigenesis was assessed using hepatitis C virus (HCV) core gene transgenic mice that spontaneously developed HCC. Male transgenic mice were treated for 5 months with either a control diet or an isocaloric TFA-rich diet that replaced the majority of soybean oil with shortening. The prevalence of liver tumors was significantly higher in TFA-rich diet-fed transgenic mice compared with control diet-fed transgenic mice. The TFA-rich diet significantly increased the expression of pro-inflammatory cytokines, as well as oxidative and endoplasmic reticulum stress, and activated nuclear factor-kappa B (NF-κB) and nuclear factor erythroid 2-related factor 2 (NRF2), leading to high p62/sequestosome 1 (SQSTM1) expression. Furthermore, the TFA diet activated extracellular signal-regulated kinase (ERK) and stimulated the Wnt/β-catenin signaling pathway, synergistically upregulating cyclin D1 and c-Myc, driving cell proliferation. Excess TFA intake also promoted fibrogenesis and ductular reaction, presumably contributing to accelerated liver tumorigenesis. In conclusion, these results demonstrate that a TFA-rich diet promotes hepatic tumorigenesis, mainly due to persistent activation of NF-κB and NRF2-p62/SQSTM1 signaling, ERK and Wnt/β-catenin pathways and fibrogenesis. Therefore, HCV-infected patients should avoid a TFA-rich diet to prevent liver tumor development.